Official Google Cloud Certified Professional Cloud Security Engineer Exam Guide : Become an Expert and Get Google Cloud Certified with This Practitioner's Guide - Chowdhary, Ankush (Packt Publishing, Limited, 2023)
Master designing, developing, and operating secure infrastructures on Google cloud Key Features Prepare for the certification exam with clear explanations, real-world examples, and self-assessment questions Review Google Cloud security best practices for building a secure and compliant cloud environment Explore advanced concepts like Security Command Center, BeyondCorp Zero Trust, and container security Book Description Google Cloud security offers powerful controls to assist organizations in establishing secure and compliant cloud environments. With this book, you'll gain in-depth knowledge of the Professional Cloud Security Engineer certification exam objectives, including Google Cloud security best practices, identity and access management (IAM), network security, data security, and security operations. The chapters go beyond the exam essentials, helping you explore advanced topics such as Google Cloud Security Command Center, the BeyondCorp Zero Trust architecture, and container security. With step-by-step explanations, practical examples, and practice exams to help you tighten up your skills for the exam, you'll be able to efficiently review and apply key concepts of the shared security responsibility model. Finally, you'll get to grips with securing access, organizing cloud resources, network and data security, and logging and monitoring. By the end of this book, you'll be proficient in designing, developing, and operating security controls on Google Cloud and gain insights into emerging concepts for future exams. What you will learn Understand how Google secures infrastructure with shared responsibility Use resource hierarchy for access segregation and implementing policies Utilize Google Cloud Identity for authentication and authorizations Build secure networks with advanced network features Encrypt/decrypt data using Cloud KMS and secure sensitive data Gain visibility and extend security with Google's logging and monitoring capabilities Who this book is for This book is for IT professionals, cybersecurity specialists, system administrators, and any technology enthusiasts aspiring to strengthen their understanding of Google Cloud security and elevate their career trajectory. We delve deep into the core elements needed to successfully attain the Google Cloud Professional Security Engineer certification--a credential that stands as a testament to your proficiency in leveraging Google Cloud technologies to design, develop, and manage a robust, secure infrastructure. As businesses increasingly migrate their operations to the cloud, the demand for certified professionals in this field has skyrocketed. Earning this certification not only validates your expertise but also makes you part of an elite group of GCP Security Engineers, opening doors to opportunities that can significantly advance your career. Whether you're seeking to gain a competitive edge in the job market, earn higher pay, or contribute at a higher level to your current organization, this book will guide you every step of the way on your journey to becoming a certified Google Cloud Professional Security Engineer.